UV reflectance is associated with environmental conditions in Palaearctic Pieris napi (Lepidoptera: Pieridae). (16th February 2017) - Stella, David; Pecháček, Pavel; Meyer‐Rochow, Victor Benno; Kleisner, Karel
Abstract: The subject of our investigation was the visual features of wing color with special focus on the UV reflectance in the green‐veined white butterfly ( Pieris napi ). Previous studies had concluded that UV reflectance on dorsal wing surfaces is found only in the female P. napi . Based on UV sensitive photography, we analyzed a correlation between 12 geographic and environmental factors and UV reflectance patterns on 3 patches on the forewings of 407 P. napi specimens from the Palaearctic region. Results had shown that females significantly differ from males: they exhibit a 25% higher UV reflectance. To investigate whether and how UV reflectance levels on the forewings and hindwings of both sexes are influenced by the environment, we performed a principal component analysis (PCA) with several environmental variables. For several variables (in particular, latitude and longitude, mean annual temperature and precipitation, and temperature annual range and altitude), the generalized linear model (GLM) model revealed a significant correlation in both sexes. This suggests a link between UV reflectance levels and the environment and distribution of P. napi . We found that stronger UV reflectance is associated with generally more hostile environments and concluded that large‐scale environmental factors influence the UV reflectance on the forewings of both male and female green‐veined white butterflies.